A New Bibliometric Index: The Top 100 Most Disruptive and Developmental Publications in Colorectal Surgery Journals - Becerra, Adan Z; Grimes, Chassidy E; Grunvald, Miles W; Underhill, Joshua M; Bhama, Anuradha R; Govekar, Henry R; Saclarides, Theodore J; Hayden, Dana M (Diseases of the colon & rectum, 2022)
A new bibliometric index called the disruption score was recently proposed to identify innovative and paradigm-changing publications. The goal was to apply the disruption score to the colorectal surgery literature to provide the community with a repository of important research articles. This study is a bibliometric analysis. The 100 most disruptive and developmental publications in Diseases of the Colon & Rectum, Colorectal Disease, International Journal of Colorectal Disease, and Techniques in Coloproctology were identified from a validated data set of disruption scores and linked with the iCite National Institutes of Health tool to obtain citation counts. The primary outcomes measured were the disruption score and citation count. We identified 12,127 articles published in Diseases of the Colon & Rectum (n = 8109), International Journal of Colorectal Disease (n = 1912), Colorectal Disease (n = 1751), and Techniques in Coloproctology (n = 355) between 1954 and 2014. Diseases of the Colon & Rectum had the most articles in the top 100 most disruptive and developmental lists. The disruptive articles were in the top 1% of the disruption score distribution in PubMed and were cited between 1 and 671 times. Being highly cited was weakly correlated with high disruption scores (r = 0.09). Developmental articles had disruption scores that were more strongly correlated with citation count (r = 0.18). This study is subject to the limitations of bibliometric indices, which change over time. The disruption score identified insightful and paradigm-changing studies in colorectal surgery. These studies include a wide range of topics and consistently identified editorials and case reports/case series as important research. This bibliometric analysis provides colorectal surgeons with a unique archive of research that can often be overlooked but that may have scholarly significance. See Video Abstract at http://links.lww.com/DCR/B639.UN NUEVO INDICE BIBLIOMÉTRICO: LAS 100 MAS IMPORTANTES PUBLICACIONES EN INNOVACIONES DESESTABILIZADORAS Y DE DESARROLLO EN LAS REVISTAS DE CIRUGÍA COLORRECTALANTECEDENTES:Un nuevo índice bibliométrico llamado innovación desestabilizadora y de desarrollo ha sido propuesto para identificar publicaciones de vanguardia y que pueden romper paradigmas.OBJETIVO:La meta fué aplicar el índice de desestabilización a la literature en cirugía colorectal para aportar a la comunidad con un acervo importante de artículos de investigación.DISEÑO:Un análisis bibliométrico.PARAMETROS:Las 100 publicaciones mas desestabilizadores y de desarrollo en las revistas: Diseases of the Colon and Rectum, Colorectal Disease, International Journal of Colorectal Disease, y Techniques in Coloproctology se recuperaron de una base de datos validada con puntuaciones de desestabilización y se ligaron con la herramienta iCite NIH para obtener la cuantificación de citas.PRINCIPAL MEDIDA DE RESULTADO:El índice desestabilizador y la cuantificación de citas.RESULTADOS:Se identificaron 12,127 articulos publicados en Diseases of the Colon and Rectum (n = 8,109), International Journal of Colorectal Disease (n = 1,912), Colorectal Disease (n = 1,751), y Techniques in Coloproctology (n = 355) de 1954-2014. Diseases of the Colon and Rectum representó la mayoría de las publicaciones dentro de la lista de los 100 mas desestabilizadores y de desarrollo. Esta literatura desestabilizadora se encuentra en el principal 1% de la distribución de la puntuacón desestabilizadora en PubMed y se citaron de 1 a 671 veces. El ser citado con frecuencia se relacionó vagamente con las puntuaciones de desastibilización (r = 0.09). Los artículos de desarrollo tuvieron puntuaciones de desestabilización que estuvieron muy correlacionados con la cuantificación de las citas (r = 0.18).LIMITACIONES:Las sujetas a las limitaciones de los índices bibliométricos, que se modifican en el tiempo.DISCUSION:La putuación de desestabilicación identificó trabajos perspicaces, pragmáticos y modificadores de paradigmas en cirugía colorrectal. Es de interés identificar que se incluyeron una gran variedad de temas y en forma consistente editoriales, reportes de casos y series de casos que representaron una investigación importante. Este análisis bibliométrico aporta a los cirujanos colorrectales de un acervo de investigación único que puede con frecuencia pasarse por alto, y sin embargo tener una gran importancia académica. Consulte Video Resumen en http://links.lww.com/DCR/B639. (Traducción- Dr. Miguel Esquivel-Herrera).